DETERMINING OPTIMUM LIVESTOCK (CATTLE) FLOW IN TURKEY USING SPATIAL EQUILIBRIUM MODEL - A. Keskin (Journal of Animal and Plant Sciences, 2019)
The share of cattle meat production by agricultural regions in Turkey has shown significant variations from 1963 to date. This had a positive effect in some regions while some other regions were impacted negatively in terms of the cattle meat production and thus led to variations in the cattle meat production. Within this context, this study intends to determine the optimum livestock cattle between agricultural regions. Turkey Cattle Breeding Spatial Equilibrium Model in Turkey for 2016 was formulated for this purpose. This model formed by using the supply & demand functions and inter-regional transportation costs was analyzed by the GAMS software. According to the results of the analysis, it was established that in 2016; there was a cattle flow from Northeastern, Southeastern and Central - Eastern regions towards the other regions. In 2016, Marmara regions procured 48.8% of its cattle requirement and Aegean Region procured 26.4% of its cattle requirement from the Northeastern Region. The Mediterranean Region met 16.3% of its cattle demand from Northeastern Region, 29.5% of its requirement from Southeastern Region and 12.2% of its need from Central – Eastern Region. Black sea and Central Southern Regions met their cattle requirements from the Central eastern regions by 3.6% and 22.8% respectively.
Keywords: Spatial equilibrium model; cattle industry; production flow; Turkey